Could changing hiring practices help more women climb the corporate ladder? - Hicks, Maureen Soyars (Monthly Labor Review, 2020)
The article examines how changing hiring practices help more women in the corporate sector in the U.S. It mentions about working paper by economists including Joyce He, Sonia Kang, and Nicola Lacetera of National Bureau of Economic Research, in November, 2019 which investigated whether different gender attitudes toward competition affect who applies for promotions.